Aging of Wood for Musical Instruments: Analysis of Changes in Color, Surface Morphology, Chemical, and Physical-Acoustical Properties during UV and Thermal Exposure - Gurau, Lidia; Timar, Maria Cristina; Cosereanu, Camelia; Cosnita, Mihaela; Stanciu, Mariana Domnica (MDPI AG, 2023)
The acoustic features of old resonance wood in violins exhibit a superior quality when compared to those from new resonance wood. This study focuses on an assessment of the sound quality of two types of wood for musical instruments, spruce and maple (class A and D), before and after aging via thermal and UV exposure. The samples were characterized before and after UV aging in terms of color change (using a Chroma meter), surface morphology (using a MarSurf XT20 instrument), chemical changes (monitored by FTIR spectroscopy), and sound propagation speed (using an ultrasound device). After UV treatment, the wavier surface increased the area of exposure and degradation. Also, the color changes were found to be more accentuated in the case of spruce compared to sycamore maple. The FTIR results indicated more advanced aging processes for spruce when compared to maple under the same experimental conditions. This difference resulted mostly from the increased formation of carbonyl-containing chromophores via oxidative processes in spruce rather than in maple, which is in agreement with the color change findings. Exposure of both species to thermal and UV radiation led to an increase in sound propagation speed, both longitudinally and radially, and to a greater extent in wood quality class A when compared to quality class D.
Keywords: resonance wood; acoustic quality; sound propagation; UV aging; color changes; chemical changes; surface morphology